2020
DOI: 10.1017/s1751731119003392
|View full text |Cite
|
Sign up to set email alerts
|

Do farming conditions influence brominated flame retardant levels in pig and poultry products?

Abstract: Brominated flame retardants (BFR) are primarily used as flame retardant additives in insulating materials. These lipophilic compounds can bioaccumulate in animal tissues, leading to human exposure via food ingestion. Although their concentration in food is not yet regulated, several of these products are recognised as persistent organic pollutants; they are thought to act as endocrine disruptors. The present study aimed to characterise the occurrence of two families of BFRs (hexabromocyclododecane (HBCDD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Huneau‐Salaün et al. ( 2020 ) investigated if farming conditions influenced BFR levels in pig and poultry products. In a monitoring study conducted in France from 2013 to 2015, they measured the levels of the eight PBDEs considered to be of primary interest in the previous Opinion in samples from 60 hen egg farms (34 without an open‐air range and 26 free‐range), 57 broiler farms (27 without an open‐air range and 30 free‐range) and 42 pig farms without an open‐air range in relation to their rearing environments.…”
Section: Assessmentmentioning
confidence: 99%
“…Huneau‐Salaün et al. ( 2020 ) investigated if farming conditions influenced BFR levels in pig and poultry products. In a monitoring study conducted in France from 2013 to 2015, they measured the levels of the eight PBDEs considered to be of primary interest in the previous Opinion in samples from 60 hen egg farms (34 without an open‐air range and 26 free‐range), 57 broiler farms (27 without an open‐air range and 30 free‐range) and 42 pig farms without an open‐air range in relation to their rearing environments.…”
Section: Assessmentmentioning
confidence: 99%
“…In a monitoring study conducted in France from 2013 to 2015, Huneau‐Salaun et al. (2020) measured the levels of HBCDDs in 60 hen egg farms (34 without an open‐air range and 26 free‐range), 57 broiler farms (27 without an open‐air range and 30 free‐range) and 42 pig farms in relation to their rearing environments. The authors measured the levels of HBCDDs in eggs, broiler muscle and pig muscle and found that α‐HBCDD was the most frequently detected stereoisomer found in eggs, broiler muscle and pig muscle, while β‐HBCDD was reported in broilers muscles, and γ‐HBCDD in broiler and pig muscle.…”
Section: Assessmentmentioning
confidence: 99%